2017
DOI: 10.1021/acssynbio.7b00249
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Terpenoid-Production Platform in Streptomyces reveromyceticus SN-593

Abstract: Terpenoids represent the largest class of natural products, some of which are resources for pharmaceuticals, fragrances, and fuels. Generally, mass production of valuable terpenoid compounds is hampered by their low production levels in organisms and difficulty of chemical synthesis. Therefore, the development of microbial biosynthetic platforms represents an alternative approach. Although microbial terpenoid-production platforms have been established in Escherichia coli and yeast, an optimal platform has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…As prokaryotes, Streptomyces are relatively easy to manipulate and culture, allowing for the improved and sustainable production of certain chemicals [154]. For example, a terpenoid-production platform was recently developed for Streptomyces reveromyceticus and the titer of botryococcene (a triterpene) was increased by manipulating biosynthetic genes and promoters [155]. It has been reported that VOC biosynthesis is commonly catalyzed by products of single genes rather than gene clusters [16,17,156,157], further simplifying the complexity of gene manipulations required for improving yields.…”
Section: Discussionmentioning
confidence: 99%
“…As prokaryotes, Streptomyces are relatively easy to manipulate and culture, allowing for the improved and sustainable production of certain chemicals [154]. For example, a terpenoid-production platform was recently developed for Streptomyces reveromyceticus and the titer of botryococcene (a triterpene) was increased by manipulating biosynthetic genes and promoters [155]. It has been reported that VOC biosynthesis is commonly catalyzed by products of single genes rather than gene clusters [16,17,156,157], further simplifying the complexity of gene manipulations required for improving yields.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has recently reported the engineering of methylotrophic yeast P. pastoris for the biosynthesis of the squalene-derived (+)-ambrein, yielding 105 mg L −1 (Moser et al 2018). Other hosts were modified to produce botryococcene in a similar range, such as Streptomyces reveromyceticus SN-593, a strain with a native mevalonate operon, that upon fine-tuning of expression of its global regulator of terpenoid biosynthesis, Fur22, yielded 212 mg L −1 (Khalid et al 2017). Rhodobacter capsulatus produced 110 mg L −1 of botryococcene in an autotrophic cultivation setup supplying only CO 2 , H 2 , and O 2 that yielded almost threefold more in titer compared with a glucose-based fed batch (Khan et al 2015).…”
Section: Microbial Production Of Different Terpenoid Classesmentioning
confidence: 99%
“…In addition to MK biosynthesis, isoprenoids are critical for the biosynthesis of membrane lipids, carotenoids, sterols, and other components of the bacterial cell wall (Oldfield, 2010). Isopentenyl-PP, one of the substrates of HepT and the starting molecule for other isoprenoid biosynthesis, is synthesized either via 2-C-methyl-D-erythritol-4-phosphate (MEP) and/or mevalonate pathway (Lange et al, 2000;Khalid et al, 2017). The enzymes of the MEP pathway have been used as targets for antibiotic discovery against microbes that harbor the MEP pathway (Shigi, 1989;Jomaa et al, 1999).…”
Section: Longer Chain Mks Producing S Aureus Are Hypersensitive To Lmentioning
confidence: 99%